2007
DOI: 10.5172/jamh.6.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Helping Friends: a peer support program for senior secondary schools

Abstract: Peer support is used frequently in addressing the health of young people. Helping Friends builds on the existing peer helping networks in schools to improve the availability, accessibility and appropriateness of social and personal support. It increases young people's knowledge of and access to referral options (in and out of school) and assists in the development of a safe and supportive school environment. Twenty-two schools in North Queensland, Australia participated in the program with many participating o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Issues addressed are: altruistic attitudes in children (Frydman et al 1995) the social acceptance of children with special needs (Circle of friends, Frederickson and Turner 2002), social and personal support (Helping Friends, Dillon and Swinbourne 2007), positive peer culture (Opp et al 2007), strength-based program (Heckenlaible-Gotto andRoggow 2007), the social interaction skills of children with Asperger syndrome (SODA, Bock 2007); cooperative learning (Putnam et al 1996), structured cooperative learning (Gillies 2004), Jigsaw classroom environment (Walker and Crogan 1998), peer-mediated instruction and peer tutoring and their application for special needs pupils (Maheady et al 1991;Kamps et al 1998).…”
Section: Helpfulnessmentioning
confidence: 99%
“…Issues addressed are: altruistic attitudes in children (Frydman et al 1995) the social acceptance of children with special needs (Circle of friends, Frederickson and Turner 2002), social and personal support (Helping Friends, Dillon and Swinbourne 2007), positive peer culture (Opp et al 2007), strength-based program (Heckenlaible-Gotto andRoggow 2007), the social interaction skills of children with Asperger syndrome (SODA, Bock 2007); cooperative learning (Putnam et al 1996), structured cooperative learning (Gillies 2004), Jigsaw classroom environment (Walker and Crogan 1998), peer-mediated instruction and peer tutoring and their application for special needs pupils (Maheady et al 1991;Kamps et al 1998).…”
Section: Helpfulnessmentioning
confidence: 99%
“…While prior research has established the academic benefits of peer tutoring, there is a paucity of research on the effectiveness of other forms of peer support, and the research that has been conducted has largely been descriptive and informal (Cowie and Wallace 2000;Dillon and Swinbourne 2007). In the United Kingdom, peer support interventions are widely used as a means of combating bullying in schools (Cowie and Hutson 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Intervention studies reported diverse intervention activities for building resilience-promoting assets and resources on the individual, peer, and community levels, particularly through group-based activities. Given the central role that peers and supportive friends play in protecting against diminished mental health and other problems and in building resilience for Indigenous adolescents (49,97), group-based interventions are a promising approach for enhancing Indigenous adolescent resilience in school settings (74,75,79,85). Group-based program activities also fostered a connection with caring adults, such as program facilitators, Elders, and other community members.…”
Section: The Translation Of Theory Into Intervention Activitiesmentioning
confidence: 99%